Visual-motor integration, visual perception, and fine motor coordination in a population of children with high levels of Fetal Alcohol Spectrum Disorder. (August 2016) - Doney, Robyn; Lucas, Barbara R.; Watkins, Rochelle E.; Tsang, Tracey W.; Sauer, Kay; Howat, Peter; Latimer, Jane; Fitzpatrick, James P.; Oscar, June; Carter, Maureen; Elliott, Elizabeth J.
Highlights: Many children in our cohort had poor visual-motor integration (VMI) skills, regardless of whether they had prenatal alcohol exposure (PAE) or Fetal Alcohol Spectrum Disorder (FASD). Visual perception was 'average' in all groups; and fine motor coordination 'average' in all groups other than children with FASD. Children with FASD had 'below average' fine motor coordination than children without PAE or PAE (no FASD). Both VMI and fine motor coordination should be assessed in children with PAE, and during FASD diagnostic assessment. Many Aboriginal children in remote regions may benefit from therapeutic support for VMI deficits to improve handwriting and other classroom skills, which may improve academic performance. Abstract: Background: Visual-motor integration (VMI) skills are essential for successful academic performance, but to date no studies have assessed these skills in a population-based cohort of Australian Aboriginal children who, like many children in other remote, disadvantaged communities, consistently underperform academically. Furthermore, many children in remote areas of Australia have prenatal alcohol exposure (PAE) and Fetal Alcohol Spectrum Disorder (FASD), which are often associated with VMI deficits. Methods: VMI, visual perception, and fine motor coordination were assessed using The Beery-Buktenica Developmental Test of Visual-Motor Integration, including its associated subtests of Visual Perception and Fine Motor Coordination, in a cohort of predominantly Australian Aboriginal children (7.5–9.6 years, n = 108) in remote Western Australia to explore whether PAE adversely affected test performance. Cohort results were reported, and comparisons made between children i) without PAE; ii) with PAE (no FASD); and iii) FASD. The prevalence of moderate (≤16th percentile) and severe (≤2nd percentile) impairment was established. Results: Mean VMI scores were 'below average' (M = 87.8 ± 9.6), and visual perception scores were 'average' (M = 97.6 ± 12.5), with no differences between groups. Few children had severe VMI impairment (1.9%), but moderate impairment rates were high (47.2%). Children with FASD had significantly lower fine motor coordination scores and higher moderate impairment rates (M = 87.9 ± 12.5; 66.7%) than children without PAE (M = 95.1 ± 10.7; 23.3%) and PAE (no FASD) (M = 96.1 ± 10.9; 15.4%). Conclusions: Aboriginal children living in remote Western Australia have poor VMI skills regardless of PAE or FASD. Children with FASD additionally had fine motor coordination problems. VMI and fine motor coordination should be assessed in children with PAE, and included in FASD diagnostic assessments.